Water-Dispersible Phytosterol Nanoparticles: Preparation, Characterization, and in vitro Digestion - Li, Ao; Zhu, Aixia; Kong, Di; Wang, Chunwei; Liu, Shiping; Zhou, Lan; Cheng, Ming (Frontiers in Nutrition, 2022)
For improving solubility and bioaccessibility of phytosterol (PS), phytosterol nanoparticles (PNPs) were prepared by emulsification-evaporation combined high pressure homogenization method. The organic phase was formed with the dissolved PS and soybean lecithin (SL) in anhydrous ethanol, then mixed with soy protein isolate (SPI) solution and homogenized into nanoparticles, followed by the evaporation of ethanol. The optimum fabrication conditions were determined as PS (1%, w/v): SL of 1:4, SPI content of 0.75% (w/v), and ethanol volume of 16 mL. PNPs were characterized to have average particle size 93.35 nm, polydispersity index (PDI) 0.179, zeta potential -29.3 mV and encapsulation efficiency (EE) 97.3%. The impact of temperature, pH, and ionic strength on the stability of fabricated PNPs was determined. After 3 h in vitro digestion, the bioaccessibility of PS in nanoparticles reached 70.8%, significantly higher than the 18.2% of raw PS. Upon freeze-drying, the particle size of PNPs increased to 199.1 nm, resulting in a bimodal distribution. The solubility of PS in water could reach up to 2.122 mg/mL, approximately 155 times higher than that of raw PS. Therefore, this study contributes to the development of functional PS-food ingredients.